Mathematical matrix method to predict project total cost & schedule - Ty, P. (Research India Publications, 2014)
Traditionally the prediction of total project cost and schedule/time followed different methods and was based on the schedule of quantities and labors and on quantity of work and productivity, respectively. The major deficiency of the methods was that the calculations were independent. Change in schedule was not reflected in cost and vice versa i.e. the methods were not integrated. Many researches have been carried out on the integration of cost and schedule to provide consistency in the evaluation of cost and schedule. Changes in schedule automatically reflected on the cost of the project. The integration of cost and schedule requires project management breakdown structure, project breakdown structure, agreed schedule and resources. Models developed by Lee and Yi (1999) and Chen (2008) were robust but did not include all the factors. The integrated technique has also not been applied to offshore projects. The nature of offshore projects and difficulties in developing the project breakdown structure were the main challenges. The present work includes four uncertain factors which affect the cost/schedule namely time value of money, resource allocation cost, overhead cost and weather and applies them in the cost and schedule evaluation of an offshore pipe-work project. The objectives of the work were to integrate the offshore project breakdown structure, to predict the total cost and schedule using the mathematical matrix method and apply the earned value method in conjunction with the matrix method for project monitoring and control. The case study on offshore pipe work project of 3 wells show a predicted cost of RM8329122 for well drilling time of 28-28-28 days. For well drill times of 60- 60-60 days, the total cost was RM9192546, showing a variation of 10.37 in cost for different drilling times, 13 for overhead cost (since it was evaluated as a percentage of the total cost); 4.44 increase for 12 time value of investment; 0.72 for 5 resource allocation factor; and 0.38 for 6 impacted days of work. The variation on budget cost is very small due to the resource allocation cost and weather whereas it is significant due to the overhead cost and time value of investment. The use of EVM using mathematical matrix method for project monitoring and control was also demonstrated. Â© Research India Publications.